Trade Marks and Performance in UK Firms: Evidence of Schumpeterian Competition through Innovation. - Greenhalgh, C; Rogers, M (Department of Economics (University of Oxford), 2007)
This paper uses a novel data set of the trade mark activity of UK manufacturing and service sector firms to investigate whether applications for trade marks are suggestive of product innovation, improving the profitability and productivity of firms. Data on both trade (and service) marks sought via the UK Patent Office (UKTM) and the European Community Office for Harmonisation of the Internal Market (CTM) are available. There was rapid growth in trade mark activity during the period covered by the data (1996-2000). We first analyse Tobin’s q, the ratio of stock market value to the book value of tangible assets, as the market value of the firm should reflect the expected future return on intangible assets. We explore the impact of undertaking any trade mark activity and also the effects of increasing trade mark intensity among those who do. The results indicate that stock market values are positively associated with R&D; and trade mark activity by firms. We find larger differences between firms with and without trade marks for services than for manufacturing. We also find bigger differences in Tobin’s q when the services firm is applying for Community marks, rather than just applying for UK marks. Increasing the intensity of Community trade marking appears to raise market value for both manufacturing and services, but this relationship weakened over the 1996 to 2000 period. The second part of this paper investigates the relationship between trade mark activity and productivity, using a value added production function. The results indicate that firms that trade mark have significantly higher value added than non-trade markers (by between 10% and 30% across all firms). Our interpretation is that trade mark activity proxies a range of other, unobservable, firm-level characteristics including innovation that raise productivity and product unit values. We also analyse whether greater trade mark intensity raises productivity growth. Higher trade mark intensity has some positive association with productivity growth, particularly in services, but the results are relatively weak. These results seem broadly consistent with those derived using the market value approach, suggesting that stock markets are efficient in estimating the likely benefits of new intangible assets, and that managers were not just seeking trade marks to follow a management fad, but could expect to receive real returns from innovative activity leading to new products requiring trade marks. Even so, the marginal returns to extra trade marks per firm were diminishing quite rapidly over the period, as indicated by our exploration of the interaction of time trends with trade mark intensity. In the final section of the paper we examine interactions between firms IP activity to explore the nature of creative destruction and simultaneous growth via innovation. We find that, in the short run, greater IP activity by other firms in the industry reduces the value added of the firm, but this same competitive pressure has later benefits via productivity growth and this is reflected in higher stock market value. This describes the Schumpeterian process of competition through innovation restraining profit margins while increasing product variety and quality.